THE EFFECT OF FINANCIAL AND NON-FINANCIAL FACTORS ON THE LEVEL OF UNDERPRICING AND OVERPRICING IN INITIAL CONDUCTING COMPANIESPUBLIC OFFERINGS ON THE INDONESIA STOCK EXCHANGE IN 2019-2022 - Irgi Adyatma Fahrezy; Khaira Amalia Fachruddin; Syahyunan (CV. Radja Publika, 2024)
The number of public companies in Indonesia are 898 companies and as many as 213 or 23.7 percent of these companies conducted Initial Public Offerings (IPOs) in the 2019 – 2022 period, as many as 187 companies experienced underpricing and 26 companies experienced overpricing on the first day of listing on the stock exchange. This makes Indonesia one of the countries with the most active IPO market in the respective period. The purpose of this study is to find out the factors that affect the level of underpricing and overpricing, such as financial and non-financial factors. The sample of this study is all IPO companies in the period 2019 – 2022 with a mix research method by conducting quantitative data analysis through secondary data from the Indonesia Stock Exchange (IDX) and qualitative data analysis with intensive interviews with 3 actor informants on the IPO stock exchange. The results of this study are that the size of the company and the inflation rate have a negative and significant effect on underpricing, with proceed and hot issue having a positive and significant effect on overpricing with the age of the company having a significant negative effect on overpricing, other variables return on assets, current ratio, proceed, Underwriter reputation, investor sentiment, hot issues, company age do not have a significant effect on underpricing as well as return on assets, current ratio, company size, underwriter reputation, inflation rate, investor sentiment do not have a significant effect on overpricing.